The role of automatic stabilizers in business cycle: The case of Indonesia - Haryo Kuncoro (European Journal of Government and Economics (EJGE), 2021)
The use of large fiscal stimulus packages to dampen the impact of Covid-19 recently has raised concerns about the effectiveness of the discretionary fiscal policy. This paper aims at analysing the feasibility of automatic fiscal stabilisers to mitigate economic fluctuations in the case of Indonesia. Using the IMF standard model for quarterly data over the period of 2001(1) to 2019(4), we find that the role of automatic fiscal stabilisers is getting greater both in revenue and spending. This implies that the automatic fiscal stabilisers are feasible as the main fiscal policy instrument for economic stability goals in the future. However, given the existing circumstances, Indonesia has to reform economic, regulatory, and institutional ecosystems in adopting the automatic fiscal stabilisers.
Keywords: E32; E62; H61; H62; 330; automatic stabilisers; business cycle; discretionary fiscal policy; government spending; taxes